PDK4 Inhibition Ameliorates Melatonin Therapy by Modulating Cerebral Metabolism and Remyelination in an EAE Demyelinating Mouse Model of Multiple Sclerosis - Ghareghani, Majid; Farhadi, Zahra; Rivest, Serge; Zibara, Kazem (Frontiers in Immunology, 2022)
We recently showed that melatonin ameliorates the severity of experimental autoimmune encephalomyelitis (EAE), an animal model of MS. However, efficiency of melatonin therapy was associated with side effects, manifested by slowing down of remyelination, through increasing the inhibitory effects of brain pyruvate dehydrogenase kinase-4 (PDK-4) on pyruvate dehydrogenase complex (PDC), a key enzyme in fatty acid (FA) synthesis during remyelination. In this study, we investigated the metabolic profile of FA synthesis using combination therapy of melatonin and diisopropylamine dichloroacetate (DADA), a PDK4 inhibitor, in EAE mice. Disease progression was monitored by recording the disability scores. Immunological, oligodendrogenesis and metabolic factors were also evaluated. Results showed that combination therapy of melatonin and DADA significantly reduced EAE disability scores, compared to melatonin, whereas DADA alone did not have any effect. In addition, co-therapy inhibited pro-inflammatory while increasing anti-inflammatory cytokines, significantly better than melatonin alone. Moreover, administration of combination drugs recovered the declined expression of oligodendrocytic markers in EAE, more potently than melatonin. Furthermore, co-therapy affected cerebral energy metabolism by significantly reducing lactate levels while increasing N-acetylaspartate (NAA) and 3-hydroxy-3-methyl-glutaryl-coenzyme-A reductase (HMGCR) levels. Finally, while melatonin increased lactate and PDK4 expression levels and greatly reduced PDC activity, co-therapy significantly restored PDC function while reducing the lactate levels. In summary, administration of melatonin with DADA increased the efficiency of melatonin treatment by eliminating the inhibitory effects of PDK4 on PDC’s function, a critical step for proper FA synthesis during remyelination.